Analysis of the Influence of Customer Relationship Management and Service Quality on Customer Loyalty at Avia Tour, Summarecon Mall Serpong - Widjaya, Sylviana; Ritonga, Roozana Maria (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Tourism is an activity conducted by individuals or groups to enjoy destinations with cultural, unique, or historical attractions. This study examines the influence of Customer Relationship Management (CRM) and service quality on customer loyalty at Avia Tour. The research adopts a quantitative approach using descriptive methods, with Avia Tour customers as the research subjects. The results show that CRM and service quality significantly influence customer loyalty. Effective customer relationship management and high-quality service collectively contribute to increasing customer loyalty at Avia Tour. In conclusion, both variables positively and significantly impact customer loyalty.